Analisis Manajemen Program Mujahadah dan Pembibitan Tahfizhul Qur’an - Doni Susanto (Studia Manageria, 2022)
This study aims not only to assist students in achieving or improving the quality of memorizing the Al-Qur'an, which they mastered while studying at the Aliyah madrasah, but also to prepare alumni who will be able to continue their studies abroad, knowledgeable but adhering to the "aqeedah ahlussunnah wal jama'ah." This study used the descriptive-qualitative method. The data collection technique uses interview, observation, and documentation techniques. After the data is collected, data reduction, data presentation, and conclusions are drawn. Checking the validity of the data using triangulation and reference materials The Al-Ittifaqiah Indralaya Mujahadah and Nursery Program (MABIT) is a preparatory program for studies in the Middle East and Europe with various models or program classes. So that the Management of the MABIT Al-Ittifaqiah Indralaya Program is a forum or institution for managing educational programs in Al-Ittifaqiah Indralaya and is based on professional management, starting from program planning, program organization, program implementation, and program supervision.